Genetic and morphological diversity in Cousinia cylindracea (Asteraceae) populations: Identification of gene pools - AMIR ABBAS MINAEIFAR; MASOUD SHEIDAI; FARIDEH ATTAR (Biodiversitas Journal of Biological Diversity, 2015)
Minaeifar AA, Sheidai M, Attar F. 2015. Genetic and morphological diversity in Cousinia cylindracea (Asteraceae)populations: Identification of gene pools. Biodiversitas 16: 288-294. Cousinia is one of the largest genera in the Asteraceae family. Itcontains 600 to 700 species distributed in Southwest and Central Asia. In Iran with 270 species it is the largest genus after Astragalus,.Cousinia probably is unique in the degree of diversification of all its parts and high numbers of species in restricted area. In thisinvestigation 90 plant specimens of 10 geographical populations of Cousinia cylindracea Boiss. were studied from morphological andgenetic (ISSR) points of view. Both intra and inter-population morphological and genetic variability was observed in the studiedpopulations. ANOVA and CVA tests revealed significant morphological difference among these populations. Similarly, AMOVA testsrevealed significant molecular difference among geographical populations. Mantel test produced significant positive correlation betweengenetic distance and geographical distance of the studied populations. Networking, STRUCTURE analysis and population assignmenttest revealed low degree of gene flow among these populations. The results identified two different gene pools of C. Cylindracea in Iran,supporting Rechinger suggestion that C. cylindracea might have two varieties in Iran.